Different Principles of Information Design for Three Online Financial Tasks: Localization, Comparison, and Subtraction - Ponce-Arias, H (Taylor and Francis Ltd., 2024)
This study examines design principles for how to display financial information about a consumer loan that supports locating a value (e.g., What is the annual percentage rate (APR) for an 18-month loan?), comparing two values (e.g., Is the APR for a 24-month load greater than for an 18-month loan?), or subtracting two values (e.g., What is the difference in the APR for a 24-month load and an 18-month loan?). One hundred and thirty-three college students carried out these three types of tasks at a banking site that displayed information as a list (e.g., listing the value for interest rate, monthly payment, insurance cost, APR, amount financed, and total cost for a given duration ranging from 6 to 48 months) or as one of three types of tables or matrices (containing values for each of six variables across one axis and each of eight loan durations across the other). Accuracy and response time on each of the three types of tasks was tallied for each of the four groups. Consistent with the principle of distraction minimization, the list was the best display for locating a value. Consistent with the principle of conjoint alignment, a vertical matrix (with loan duration across columns) or horizontal matrix (with loan duration across rows) was the best for comparing two values, but an interactive matrix was less effective. Consistent with the principle of canonical form, a vertical matrix (with loan duration across columns) was the best for subtracting two values. Overall, the best information display depended on the type of task, consistent with cognitive theories of information processing. © 2023 Taylor & Francis Group, LLC.